2013
DOI: 10.1016/j.surfcoat.2012.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Suspension plasma sprayed bioactive glass coatings: Effects of processing on microstructure, mechanical properties and in-vitro behaviour

Abstract: International audienceBioactive glass coatings deposited via suspension plasma sprayingwere studied to improve the adhesion between orthopaedic implants and bone. Fine powders of a bioactive glass, named BG_Ca, having composition (in wt.%): 4.7 Na2O, 42.3 CaO, 6.1 P2O5, and 46.9 SiO2, were produced and dispersed in ethanol to form a suspension used as a feedstock. Various sets of spray parameterswere applied in order to define the influence of the deposition process on the final coating properties. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 27 publications
1
49
0
1
Order By: Relevance
“…However the appearance of this peak takes place at longer time than that observed for the DR 63 feedstocks, as seen in figure 2. This finding agrees with recent observations reported in the literature with regard to bioglass coatings obtained by APS [29]. According to this research, which took place with different glass compositional range (without Na2O) the overall reaction mechanism observed in SBF immersion, especially in the first days of immersion, is strongly affected by the microstructure and degree of crystallinity of the coatings.…”
Section: Coating Characterisationsupporting
confidence: 92%
“…However the appearance of this peak takes place at longer time than that observed for the DR 63 feedstocks, as seen in figure 2. This finding agrees with recent observations reported in the literature with regard to bioglass coatings obtained by APS [29]. According to this research, which took place with different glass compositional range (without Na2O) the overall reaction mechanism observed in SBF immersion, especially in the first days of immersion, is strongly affected by the microstructure and degree of crystallinity of the coatings.…”
Section: Coating Characterisationsupporting
confidence: 92%
“…However, very limited numbers of papers have dealt with obtaining BG coatings by SPS technique. This research has shown that the microstructure of SPS-BG coatings is characterised by a two-zone feature: one zone associated with well-molten particles which result in dense and flat areas and another agglomerated zone made up of fine and partially sintered grains [15]. Bolelli et al have also confirmed these microstructure features of SPS-BG coatings whereas at the same time these authors highlight the significant differences of SPS and APS coating microstructures [16].…”
Section: Introductionmentioning
confidence: 72%
“…In addition, coatings microstructure is composed of a twozone feature, i.e. a first layer made up of fine agglomerated and rounded drops partially sintered and a top zone formed by molten particles which result in dense and flat areas [15].…”
Section: Bioactive Glass Coatingsmentioning
confidence: 99%
“…The BGCaMIX glass (composition: 47.3 mol% SiO 2 , 45.6 mol% CaO, 2.3 mol% K 2 O, 2.3 mol% Na 2 O, and 2.6 mol% P 2 O 5 ) was prepared by a melt-quenching route as previously reported [21,30,31]. Briefly, the commercial raw powder reagents -all reagent grade -(SiO 2 , Na 2 CO 3 , CaCO 3 , K 2 CO 3 , Ca 3 (PO 4 ) 2 by Carlo Erba Reagenti, RodanoMilano, Italy) were mixed in a laboratory shaker for 2 h and then melted at 1450 ∘ C for 1 h. The molten BGCaMIX was then quenched in water to obtain a frit which was dried at 110 ∘ C for 12 hours.…”
Section: Glass and Composites Preparationmentioning
confidence: 99%